Morphology and Parasitaemia Development of Plasmodium berghei in Balb/c Mice (Mus musculus) - Rosnizar Rosnizar; Kartini Eriani (Syiah Kuala University, 2015)
Malaria is one of the most severe public health problems worldwide. It is a leading cause of death and disease in many developing countries, where young children and pregnant women are the groups most affected. Malaria disease caused by Plasmodium parasite have symptoms that typically include fever, fatigue, vomiting and headaches. In severe cases, it can cause yellow skin, seizures, coma or death. The present study is aimed to monitoring parasitemia level and percentage of parasite morphology as parasitaemia progresses. This research used Plasmodium berghei NK strain obtained from National University of Malaysia which originally from MR4, USA. Design used in this research was completely randomized design, with 2 treatments which were mice without infection and mice with infection of P. berghei parasite. Method used in this research was staining method of thin smear of blood using Giemsa stained and observed by microscopic. Parameter of observation were morphology and development of P. berghei at different level of parasitaemia (10%, 20%, 30% and 40%). The result showed from microscopic examination of blood slides prepared from the study animals indicated that the ring form was dominant stage obtained at all different stages of infection followed by trophozoite stage. Meanwhile schizont stage was the lowest stage obtained at all different stages observed.